Resistividade elétrica de concretos com diferentes teores de escória de alto forno e ativador químico - Rosa, Dalton Wegner da (2005)
The integrity of the rebars in reinforced concrete structures is related to the chemical and physical protection provided by the concrete layer that covers the steel. The destruction of the passivation layer precedes the onset of corrosion. Once the corrosion process starts, its rate of propagation will depend on the electrical resistivity between cathode and anode and the amount of oxygen available on the cathode. Concrete resistivity is a property linked both to the chemical and physical properties of the concrete. This study investigated the effect of the addition of blast furnace slag (BFS) on the electrical resistivity of concrete and correlated the effects of this addition on the concrete compressive strength as well as on changes in the chemical composition of aqueous phase and pore structure. Test specimens were prepared using different water/binder ratios (0.35, 0.50 and 0.65) and substitutions of 50 and 70% of BFS for cement by weight. A control sample (no BFS) was also prepared. Additionally, the effect of 4% sodium sulfate (Na2SO4) in samples with 50% BFS was also investigated. The electrical resistivity of concrete was determined using the fourelectrode method (Wenner s method adapted for use in concrete). Tests of compressive strength, porosimetry, electrical conductivity in the pore solution and the concentration of ions in the aqueous phase were performed. The tests showed there is an increase in the electrical resistivity of concrete as the degree of hydration and the concentration of BFS increase. This is related to the lower specific conductivity of the pore solution and the reduction in concrete pore size, which is shown by the good correlation between these two factors. The binary mixture with 50% BFS (50E) showed the best cost/benefit ratio for strength levels of 30MPa and 50MPa at 28 days and also for the strength level of 50MPa at 91 days.